Polymeric Nanoparticles for Brain Drug Delivery - A Review - Subashini, Raman; Mahmood, Syed; Ayah, R. Hilles; Javed, M. Noushad; Azmana, Motia; AL-japairai, Khater Ahmed Saeed (Bentham Science, 2020)
Background: Blood-brain barrier (BBB) is playing a most hindering role in drug delivery to the brain. Recent research comes out with the nanoparticles approach, is continuously working towards improving the delivery to the brain. Currently, polymeric nanoparticle is extensively involved in many therapies for spatial and temporal targeted areas delivery.